Decoding the Multifaceted Potential of Artemisia monosperma: Comprehensive Insights into Allelopathy, Antimicrobial Activity, and Phytochemical Profile for Sustainable Agriculture - Mohamed A. El-Sheikh; Anfal Alsharekh; Abdulrahman A. Alatar; Humaira Rizwana (Plants, 2023)
Weeds present a significant hazard to crop production, necessitating the development of effective and sustainable strategies for weed management. Although synthetic herbicides are effective, concerns about their environmental and health impact have been raised. This study investigates the allelopathic potential, antimicrobial activity, and phytochemical profile of Artemisia monosperma. Extracts from A. monosperma proficiently impede the growth of Chenopodium murale and Amaranthus viridis, while exhibiting varying effects on crops Solanum lycopersicum and Cucumis sativus. Leaf and seed extracts demonstrate the most significant inhibition of weed growth. Interestingly, the leaf extract at a concentration of 50% inhibited weed growth in pot experiments without affecting crop growth. Moreover, extracts from A. monosperma exhibit noteworthy antifungal and antibacterial activity, with the root extract demonstrating the strongest inhibition. The root extract inhibited the mycelial growth of Colletotrichum musae by 63% as compared to control. The leaf extract exhibited the highest levels of phenolic acids, in particular gallic acid, amounting to 116.30 ppm. This study emphasizes the multifaceted potential of A. monosperma as a sustainable solution for weed management and proposes its use in crop protection. Further investigation of its practical applications and optimization of extraction methods can aid in its integration into contemporary agricultural systems, promoting both crop yield and environmental sustainability.